Biological timekeeping : clocks, rhythms and behaviour - Kumar, Vinod (Springer Nature, 2017)
This book is a concise, comprehensive and up-to-date account of fundamental concepts and potential applications of biological timekeeping mechanisms in animals and humans. It also discusses significant aspects of the organization and importance of timekeeping mechanisms in both groups. Divided into seven sections, it addresses important aspects including fundamental concepts; animal and human clocks; clock interactions; clocks and metabolism and immune functions; pineal, melatonin and timekeeping; and clocks, photoperiodism and seasonal behaviours. The book also focuses on biological clock applications in a 24x7 human society, particularly in connection with life-style associated disorders like obesity and diabetes. It is a valuable resource for advanced undergraduates, researchers and professionals engaged in the study of the science of biological timekeeping.
Keywords: Biological rhythms.; Drosophila -- Behavior.; Circadian rhythms.; elektronické knihy; electronic books